Interpreting Greek tragedy: myth, poetry, text - Segal, Charles (Cornell University Press, 2019)
This generous selection of published essays by the distinguished classicist Charles Segal represents over twenty years of critical inquiry into the questions of what Greek tragedy is and what it means for modern-day readers. Taken together, the essays reflect profound changes in the study of Greek tragedy in the United States during this period-in particular, the increasing emphasis on myth, psychoanalytic interpretation, structuralism, and semiotics.This generous selection of published essays by the distinguished classicist Charles Segal represents over twenty years of critical inquiry into the questions of what Greek tragedy is and what it means for modern-day readers. Taken together, the essays reflect profound changes in the study of Greek tragedy in the United States during this period-in particular, the increasing emphasis on myth, psychoanalytic interpretation, structuralism, and semiotics